Rancang Bangun Mesin Pencetak Pelet Ikan Dengan Memanfaatkan Sekam Padi Sebagai Solusi Pakan Ikan - Muhamad Rikza Aldiansyah; Kardiman Kardiman; Deri Teguh Santoso (Jurnal Teknik Mesin, 2021)
The city of Karawang is famous as a city of rice granaries. As a city of rice granaries, the city of Karawang is assigned a surplus of unhulled rice of 1.5 million tons. This causes a large number of rice husks to become waste from the mills. With the knowledge and skills of farmers who are still minimal in utilizing rice husk waste, most of the rice husk waste by farmers is only thrown away or burned so that it can cause environmental pollution around the disposal of rice husk waste. One way to utilize rice husk waste is to process rice husk waste into animal feed. An alternative to solve this problem is by making a fish pellet printer that is used to produce fish pellets using rice husks as the basic ingredient. This fish pellet printing machine is made with the aim of utilizing rice husk waste which is only thrown away or burned by farmers so that rice husk waste can become a high-value product. In this study, data collection techniques were carried out by studying literature and conducting experiments on fish pellet making machines. After that, the design of the shape was carried out then continued with the manufacture / assembly of components of the fish pellet printing machine and finally the testing of tools / machines with parameters was designed and equipped with an electric motor 250 watts 220 volts 1400 rpm so that it can be used in industry. at home, this electric motor aims to act as a screw driver which is assisted by a WPA gearbox with a ratio of 1:30 so that the rotation obtained is not too fast, the rotation speed can be adjusted by the amount of pulley used so that it can be in accordance with your wishes. With these conditions, it will greatly assist producers in carrying out and speeding up the process of grinding fish pellets.